Experimental Volume Incidence Study and the Relationship of Polypropylene Macrofiber Slenderness to the Mechanical Strengths of Fiber-Reinforced Concretes - Del Savio, Alexandre Almeida (2022)
An experimental study was conducted to examine the mechanical strengths of concretes with straight high-strength knurled polypropylene macrofibers. Incidences of concrete mechanical strengths were determined for three different fiber dosages and lengths. In addition, compressive, indirect-splitting-test tensile, and flexural strengths were determined through testing. The results showed no statistically significant correlation between the volume and length of fibers with the compressive strength of polypropylene fiber-reinforced concrete (PPFRC). However, there was a statistically significant correlation between the split tensile strength, the volume, and the length of the fibers when the volume was greater than 0.80%, and the length of the fibers was greater than 50 mm. Furthermore, the modulus of rupture increased when the volume of fibers was greater than 0.80% and the length of the fibers was 60 mm. Finally, equations were proposed to determine the tensile strength by split test and the modulus of rupture as a function of the mixture’s resistance without fibers, the fibers’ volume and length.